Addressing Problem Behavior at Recess Using Peer Praise Notes. (April 2017) - Teerlink, Elise; Caldarella, Paul; Anderson, Darlene H.; Richardson, Michael J.; Guzman, E. Geovanni
School recess, though beneficial to students in many ways, can be a problematic setting due to inadequate supervision, structure, and safety. A peer praise note (PPN) intervention was implemented on the recess playground to address these concerns at a Title I elementary school. Researchers used a single-subject reversal design across all students to evaluate intervention effectiveness. Results included overall improvements in the level, trend, and variability of office discipline referrals (ODRs), especially from reversal to reinstatement of the intervention, and an effect size (percentage of data points exceeding the median; PEM) suggesting that PPNs effectively decreased ODRs. Results from social validity surveys completed by recess aides and students indicated participants' perceptions that PPNs helped improve student behavior and peer relations, communicate playground rules, extend supervision responsibilities, and offer structured activity to peer praisers. Limitations, future research, and implications are addressed.